The watcher in the woods [videorecording (DVD)] - Huston, Anjelica; Evans, Tallulah; Galitzine, Nicholas; Randall, Florence Engel, 1917- (A & E Television Networks, 2018)
A thrilling reimagining of the '80s cult classic film for a new generation. A family rents a British countryside manor for the summer, and strange occurrences unnerve them as they discover the dark past hidden by the townspeople.